2003
DOI: 10.1021/jp0225931
|View full text |Cite
|
Sign up to set email alerts
|

Post-steam-treatment of Mo/HZSM-5 Catalysts:  An Alternative and Effective Approach for Enhancing Their Catalytic Performances of Methane Dehydroaromatization

Abstract: Post-steam-treatment is a facile and effective method for improving the catalytic performances of Mo/HZSM-5 catalysts in methane dehydroaromatization under nonoxidative conditions. The treatment can enhance the stability of the catalyst and also give a higher methane conversion and a higher yield of light aromatics, as well as a decrease in the formation rate of carbonaceous deposits. 27 Al, 29 Si, and 1 H multinuclear magic angle spinning nuclear magnetic resonance, X-ray photoelectron spectroscopy, X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Migration and location of Mo species, as crucial factors in MDA, are closely related to the number of Brønsted acid sites. Wang et al [157,158] also investigated the effect of post-treatment of Mo/zeolite catalysts on MDA. Their results showed that it enhances the catalyst stability and results in higher methane conversion, higher yield of light aromatics, and a decrease in the rate of coke formation.…”
Section: Optimizing the Zeolite Supportmentioning
confidence: 99%
“…Migration and location of Mo species, as crucial factors in MDA, are closely related to the number of Brønsted acid sites. Wang et al [157,158] also investigated the effect of post-treatment of Mo/zeolite catalysts on MDA. Their results showed that it enhances the catalyst stability and results in higher methane conversion, higher yield of light aromatics, and a decrease in the rate of coke formation.…”
Section: Optimizing the Zeolite Supportmentioning
confidence: 99%
“…All NMR spectra were recorded at room temperature on a Bruker DRX-400 spectrometer with a BBO MAS probe and using 4 mm ZrO 2 rotors, as reported in our previous studies [29,37,38]. 29 Si MAS NMR spectra were collected at 79.5 MHz using a 0.8 ms (p/4) pulse with a 4 s recycle delay and 1024 scans.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The authors suggested that the more the Mo species migrate into the channels, the fewer the remaining free Brönsted acid sites are left over, and the better the reactivity and stability of the Mo/HZSM-5 catalysts. Recently, Xu and Bao et al have also reported that post-steam-treatment of the Mo/HZSM-5 catalyst is another effective approach to improve the reactivity and stability of the Mo/HZSM-5 catalysts [37,38]. The improvements are attributed to the fact that there are more Mo species migrating into the channels on one hand, and part of the Brönsted acid sites are eliminated on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…The acid-base characteristics of the catalyst are important for the reaction. Hongxia Wang et al 22 revealed that poststeam-treatment could improve the catalytic performance of Mo/HZSM-5 catalysts in methane dehydroaromatization under nonoxidative conditions. Acetone is prone to be produced on the base sites, while strong acid sites are benecial to afford propionaldehyde.…”
Section: Introductionmentioning
confidence: 99%